2016
DOI: 10.1371/journal.pone.0156940
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Quantification of Peripheral Blood Cell β-Adrenergic Receptor Density and Urinary Endothelial Cell-Derived Microparticles in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a heterogeneous disease characterized by severe angiogenic remodeling of the pulmonary artery wall and right ventricular hypertrophy. Thus, there is an increasing need for novel biomarkers to dissect disease heterogeneity, and predict treatment response. Although β-adrenergic receptor (βAR) dysfunction is well documented in left heart disease while endothelial cell-derived microparticles (Ec-MPs) are established biomarkers of angiogenic remodeling, methods for easy larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Bristow et al showed loss of β 1 -ARs in the failing RV, depletion of tissue norepinephrine, and lower levels of adenylate cyclase activity at baseline and in response to stimulation, which were identical to findings in left heart failure (13). Another study recently confirmed these findings through identification of lesser numbers of βARs in circulating mononuclear cells in individuals with PAH as compared with healthy controls or those with asthma (15).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 73%
“…Bristow et al showed loss of β 1 -ARs in the failing RV, depletion of tissue norepinephrine, and lower levels of adenylate cyclase activity at baseline and in response to stimulation, which were identical to findings in left heart failure (13). Another study recently confirmed these findings through identification of lesser numbers of βARs in circulating mononuclear cells in individuals with PAH as compared with healthy controls or those with asthma (15).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 73%
“…Multiple studies have described mononuclear/macrophage-derived EVs rich in inflammatory effector molecules like cytokines, chemokines, adhesion molecules and proteases to cause alveolar wall destruction and Urine EMPs [97] Group III PH Plasma ↑Tissue factor and endoglin in EMPs [98] Group IV PH Plasma ↑Tissue factor and endoglin in EMPs [98] Plasma ↑PMPs, LMPs and EMPs [99] Asthma Blood ↑Eosinophil derived exoxomes [100,101] BALF ↑ CD63 and CD81 + exosomes carrying leukotrienes biosynthesis enzymes [102] BALF ↑Mitochondria/mitochondrial DNA in exosomes [103] BALF ↓Phosphatidylglycerol, ceramide-phosphates, and ceramides [104] ↑Sphingomyelin in exosomes…”
Section: Role Of Evs In the Pathogenesis Of Lung Diseasesmentioning
confidence: 99%
“…Rose et al showed that endothelial cell-derived MPs can act as biomarkers for right ventricular function in PAH patients, wherein the number of these particles in urine was found to be increased in PAH patients compared to healthy controls [97] (Table 1). A correlation between these urine MP biomarkers and tricuspid annular plane systolic excursion (TAPSE) was observed in PAH patients [97].…”
Section: Pulmonary Hypertension (Ph)mentioning
confidence: 99%
“…The level of CD105 + EMVs is related to severity, EC survival and angiogenesis in PH patients . The level of CD144 + EMVs is related to hemodynamic severity, pulmonary artery intima media thickness and right ventricular function . The release of CD144 + EMVs may reflect the structural destruction of the endothelium rather than an inflamed lung.…”
Section: Endothelial Microvesiclesmentioning
confidence: 99%